DIGITAL TRANSFORMATION IN NOTARY PRACTICE: IMPLEMENTATION OF ELECTRONIC CERTIFICATES FOR AUTHENTIC DEEDS BASED ON THE NOTARY OFFICE LAW - Maulita Tri Rosida; Rusdianto Sesung (RADJA PUBLIKA, 2025)
Technological developments have brought a wave of digital transformation that has spread across various sectors of life, including the world of notarial practice in Indonesia. This research is designed to examine how notaries actually implement electronic certificates (SE) in the process of creating authentic deeds. This study specifically focuses on Law Number 2 of 2014 concerning the Office of Notaries (UUJN) and examines its relationship with the Electronic Information and Transactions Law (UU ITE). The use of electronic certificates and electronic signatures (TTE) essentially offers great promise: efficiency, speed, and increased security for legal documents, a step forward that aligns with the ideals of a